A New Approach to Synthesize Zinc(II) Coordination Polymer - Zhang, Huiming; Yao, Haibo (Asian Journal of Chemistry, 2015)
A new Zn(II) coordination polymer with benzophenone-4,4'-dicarboxylic acid (H2bpdc) and 1,4-bis(imidazol-1-yl)benzene (bib) has been prepared by hydrothermal synthesis and characterized by single-crystal X-ray diffraction, infrared and elemental analysis. Complex, {[Zn(bpdc)(bib)]·2H2O}n (1), is triclinic, space group P-1 with a = 8.958(5), b = 11.336(5), c = 14.150(5) Å, a = 111.109(5), b = 95.077 (5)°, g = 98.504(5), V = 1310.0 (10) Å3, Z = 2, Mr = 579.86, Dc = 1.470 g/cm3, F(000) = 596 and μ = 0.991 mm-1. The final refinement gave R = 0.0352 and wR = 0.0964 for 5191 reflections with I > 2s(I). X-ray diffraction analysis reveals that complex 1 displays a 2D + 2D ® 3D polycatenated structure.